2011
DOI: 10.5754/hge10669
|View full text |Cite
|
Sign up to set email alerts
|

A Breakdown of the Hippo Pathway in Gastric Cancer

Abstract: A breakdown of the Hippo pathway may play a role in tumorigenesis and metastasis of gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 0 publications
2
27
0
Order By: Relevance
“…LATS family members are core components of the Hippo pathway, which has a key role in intestinal stem cells self-renewal and differentiation [18]. It has been reported that LATS1/2 has decreased expression in the colorectal carcinoma [19] and gastric cancer by promoter hypermethylation [20]. In this study, we found that LATS1/2 was down-regulated in primary appendix and colon carcinomas, which supported the findings as reported.…”
Section: Discussionsupporting
confidence: 93%
“…LATS family members are core components of the Hippo pathway, which has a key role in intestinal stem cells self-renewal and differentiation [18]. It has been reported that LATS1/2 has decreased expression in the colorectal carcinoma [19] and gastric cancer by promoter hypermethylation [20]. In this study, we found that LATS1/2 was down-regulated in primary appendix and colon carcinomas, which supported the findings as reported.…”
Section: Discussionsupporting
confidence: 93%
“…This cytoplasm-nucleus shifting is involved in cell growth regulation in response to cell-cell contact and cell density. Inactivation of Hippo signaling pathway resulted in nuclear translocation of YAP/TAZ, drove cell proliferation, inhibited cell apoptosis, and eventually led to tumorigenesis (Xu et al, 2011). Some researchers have reported that YAP1 protein increased and localized in nuclear in some human liver and prostate cancers.…”
Section: Discussionmentioning
confidence: 99%
“…In the cytoplasm, YAP/TAZ is phosphorylated and inhibited by a complex, formed by Mst1, LATS1, Mob, WW45, and the phosphorylation results in their association with 14-3-3 protein and cytoplasmic localization (Zhao et al, 2007). In the nucleus, YAP/TAZ bound to the TEAD family transcription factors and then formed a complex, which bound to the specific DNA promoter and initiate gene transcription (Xu et al, 2011). This cytoplasm-nucleus shifting is involved in cell growth regulation in response to cell-cell contact and cell density.…”
Section: Discussionmentioning
confidence: 99%
“…YAP is a key effector protein in the Hippo pathway and is negatively regulated by the Mst1/2-LATS1/2-Mob1 complex through direct phosphorylation (11). The phosphorylation of YAP (pYAP) inhibits cell proliferation; therefore, impairment of the Hippo signaling pathway has been implicated in many human cancers including gastric cancer (17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%